Transformational technologies for more uptakes of entomopathogenic nematodes - Mahfouz M. M. Abd-Elgawad (Egyptian Journal of Biological Pest Control)
Abstract Background Accelerated concern over chemical pesticides—due to health hazards, ecological pollution, and development of resistance-breaking pathotypes—has created markets for biopesticide products worldwide. Entomopathogenic nematode (EPN) products have recently attained major developments in their use, but their markets are still mostly confined to relatively few specialty crops. Their relatively high cost, occasional inconsistent efficacy, and lack of public awareness for their diverse benefits are gaps that relegate them to niche markets. Main body Transformational technologies for EPN surveys via sophisticated sampling, extraction, identification, and counting techniques could soundly characterize and employ more promising species/strains. Also, bridging the gaps can economize their usage via dual-purpose application or controlling multiple insect pests on a crop. Their simultaneous biocontrol of a variety of pests like plant-parasitic nematodes and insect pests should be considered. Their sequential and co-application with other agricultural inputs to offer additive/synergistic effects in integrated pest management (IPM) should be expanded. Such technologies should also widen spectra of EPN activity to manage further insect pests even on low-value crops such as alfalfa and maize. Classical breeding of EPNs could obtain Heterorhabditis bacteriophora-infective juveniles with so virulent and persistent superiority that application rates and consequent costs were reduced into the range of chemical insecticides. In contrast to chemicals, applying such a sustainable, non-toxic alternative biopesticide should be expanded to control Diabrotica virgifera virgifera infesting maize fields. Merits/demerits of the three EPN mass production approaches are well-known, but the related issues need to be astutely addressed for optimization. Recent examples to challenge such production issues as nematode quality/yield and cost efficiency are highlighted. Conclusion Astute exploitation of EPNs as a part of sophisticated IPM programs for crop pests is imperative. Widening their biocontrol spectra to other pest groups such as arthropods infecting low-value crops will expand their marketing. Other aspects for more uptakes of EPNs imply optimizing EPN delivery and persistence, priming them/their bioactive insecticidal compounds, and incorporating advanced technologies to reform their biocontrol with transformative impact.